Chronic Inflammation as a Central Driver of Disease Progression in Myeloproliferative Neoplasms (MPNs): A Narrative Review: Selvi Rahmawati - Selvi Rahmawati (Fakultas Kedokteran, 2026)
Myeloproliferative neoplasms (MPNs) are clonal hematologic disorders characterized by excessive proliferation of myeloid cells that potentially progress to bone marrow fibrosis and acute myeloid leukemia (AML). At the molecular level, MPNs are defined by the presence of driver mutations, particularly in the JAK2, CALR, and MPL genes, which lead to constitutive activation of the JAK–STAT signaling pathway. Activation of this pathway not only promotes hematopoietic cell proliferation but also induces inflammatory responses that play a crucial role in MPNs pathogenesis and progression. This review aims to summarize and evaluate the role of chronic inflammation in MPNs progression, including the interactions between genetic mutations, inflammatory signaling pathways, and the bone marrow microenvironment. Chronic inflammation contributes to disease progression through multiple mechanisms, including activation of signaling pathways such as JAK–STAT and NF-κB, increased production of proinflammatory cytokines, and the induction of oxidative stress that promotes genomic instability. In addition, inflammation drives remodeling of the bone marrow microenvironment into a profibrotic and immunosuppressive state, providing a selective advantage for clonal expansion and contributing to therapeutic resistance. The dynamic interplay between clonal cells, the immune system, and the microenvironment establishes a feed-forward loop that accelerates MPN progression toward leukemic transformation. The findings of this narrative review emphasize that therapeutic strategies in MPNs should not only target the genetic mutations but also need to consider the modulation of inflammation and bone marrow microenvironment as targeted-therapy complementary approaches.